The Determinants of Life Expectancy—A Case of Four Largest Cities in China - Cai, Francis; Zhang, Ge (Journal of Applied Business and Economics, 2018)
With the sample data from the four largest cities in China, we have examined various impacts of economic growth and government expenditure in health-related fields on life expectancy. Our analysis shows that several factors have contributed to the increase of average life expectancy. In summary, each additional 100 units of GDP per capita, hospital bed and healthcare technician will improve average life expectancy by 1.6 days, 1.8 days and 1 day respectively. Our research will shed some lights on factors that impact life expectancy in Chinese urbanized areas and also help to make a global comparison between metropolitan cities around the world.